Picture Books for Children : Fiction, Folktales, and Poetry. - Northrup, Mary (ALA Editions, 2012)
Providing descriptive annotations of the best children's picture books published in the last decade, this comprehensive overview is perfect for librarians, teachers, parents, daycare providers, and anyone who works with young children.